Mobile healthcare to facilitate stress and healthy life management - Hameed, Shihab Ahmed (Journal of Scientific and Engineering Research, 2017)
Nowadays, stress problems continue increasing and become worst due to its poor management and difficult access to diagnosis tool that detect stress. This project work toward developing a mobile healthcare prototype using Android studio to help in managing stress and providing a simple assessment of stress based on a valid and reliable test, DASS-21. This project tries to integrate cultural and religious with technical aspect in soling stress problem. It provides an audio for sample of Quranic verses, hadith, and moral speech to be listened by users as part of a moral stress reliever. This project offers guidance for users toward having a healthy life by calculating the needed calories and how much calories burned via pedometer sensor. This friendly user project helps users to be more aware about their stress and guide them to have a healthy way of living.